Development of a large animal model of lethal polytrauma and intra-abdominal sepsis with bacteremia. Issue 1 (1st February 2021) - O'Connell, Rachel L; Wakam, Glenn K; Siddiqui, Ali; Williams, Aaron M; Graham, Nathan; Kemp, Michael T; Chtraklin, Kiril; Bhatti, Umar F; Shamshad, Alizeh; Li, Yongqing; Alam, Hasan B; Biesterveld, Ben E
Abstract : Background: Trauma and sepsis are individually two of the leading causes of death worldwide. When combined, the mortality is greater than 50%. Thus, it is imperative to have a reproducible and reliable animal model to study the effects of polytrauma and sepsis and test novel treatment options. Porcine models are more translatable to humans than rodent models due to the similarities in anatomy and physiological response. We embarked on a study to develop a reproducible model of lethal polytrauma and intra-abdominal sepsis, which was lethal, though potentially salvageable with treatment. Methods: Our laboratory has a well-established porcine model that was used as the foundation. Animals were subjected to a rectus crush injury, long bone fracture, liver and spleen laceration, traumatic brain injury and hemorrhage that was used as a foundation. We tested various colon injuries to create intra-abdominal sepsis. All animals underwent injuries followed by a period of shock, then subsequent resuscitation. Results: All animals had blood culture-proven sepsis. Attempts at long-term survival of animals after injury were ceased because of poor appetite and energy. We shifted to an 8-hour endpoint. The polytrauma injury pattern remained constant and the colon injury pattern changed with the intention of creating a model that was ultimately lethal but potentially salvageable with a therapeutic drug. An uncontrolled cecal injury (n=4) group resulted in very early deaths. A controlled cecal injury (CCI; n=4) group had prolonged time prior to mortality with one surviving to the endpoint. The sigmoid injury (n=5) produced a similar survival curve to CCI but no animals surviving to the endpoint. Conclusion: We have described a porcine model of polytrauma and sepsis that is reproducible and may be used to investigate novel treatments for trauma and sepsis. Level of evidence: Not applicable. Animal study.